The relationship between mothers who are both working and single parents and their children's independence - Pratiwi, Wilda Rezki; Fatmawati, Fatmawati; Sari, Yunita Kartika (JOURNAL OF Mental Health Concerns, 2025)
Background: A single parent is a family consisting of a single parent, either a father or a mother, as a result of divorce or death. Single parenthood can also occur when a child is born out of wedlock and their care becomes their sole responsibility. Independence in the soul of a single parent is very necessary to carry out dual roles in the domestic sector, namely being responsible for household chores such as cooking, washing dishes and clothes, cleaning the house, preparing food for the family, caring for, raising and educating their children and in the public sector, namely having economic duties to ensure that needs are met, namely by earning a living for their family and socially, namely socializing with the community. Purpose:  To knowing how the role of a single working parent relates to a child's independence. Method: This qualitative research involved 30 single mothers and their children. The informants were single mothers, with children aged 7-15 years old as the subjects. The study was conducted in Tuweley Village, RW 1-6, Tolitoli Regency, from January to March 2025. Results: Based on interviews, it was found that each mother has a different approach to parenting their children. These differences are influenced by their educational background, socioeconomic status, family support, and personal values. Nevertheless, there is a common thread in parenting: consistent efforts to instill religious values, independent living habits, and discipline in daily life. Support from extended family, such as biological parents, siblings, or close relatives, is also a crucial factor in helping single parents raise their children. Conclusion: The role of single parents significantly influences the development of children's independence. Mothers who fulfill the dual roles of breadwinner and caregiver still strive to provide time, attention, and guidance to their children. Keywords: Child independence; Role of parents; Single parents.